Differential Fasting Plasma Glucose and Ketone Body Levels in GHRKO versus 3xTg-AD Mice: A Potential Contributor to Aging-Related Cognitive Status?. (30th May 2017) - Griffith, Chelsea M.; Macklin, Lauren N.; Bartke, Andrzej; Patrylo, Peter R.
Abstract : Cognitive function declines with age and appears to correlate with decreased cerebral metabolic rate (CMR). Caloric restriction, an antiaging manipulation that extends life-span and can preserve cognitive function, is associated with decreased glucose uptake, decreased lactate levels, and increased ketone body (KB) levels in the brain. Since the majority of brain nutrients come from the periphery, this study examined whether the capacity to regulate peripheral glucose levels and KB production differs in animals with successful cognitive aging (growth hormone receptor knockouts, GHRKOs) versus unsuccessful cognitive aging (the 3xTg-AD mouse model of Alzheimer's disease). Animals were fasted for 5 hours with their plasma glucose and KB levels subsequently measured. Intriguingly, in GHRKO mice, compared to those in controls, fasting plasma glucose levels were significantly decreased while their KB levels were significantly increased. Conversely, 3xTg-AD mice, compared to controls, exhibited significantly elevated plasma glucose levels and significantly reduced plasma KB levels. Taken together, these results suggest that the capacity to provide the brain with KBs versus glucose throughout an animal's life could somehow help preserve cognitive function with age, potentially through minimizing overall brain exposure to reactive oxygen species and advanced glycation end products and improving mitochondrial function.